2005
DOI: 10.1083/jcb.200407053
|View full text |Cite
|
Sign up to set email alerts
|

New GABAergic interneurons in the adult neocortex and striatum are generated from different precursors

Abstract: Ongoing neurogenesis in the adult mammalian dentate gyrus and olfactory bulb is generally accepted, but its existence in other adult brain regions is highly controversial. We labeled newly born cells in adult rats with the S-phase marker bromodeoxyuridine (BrdU) and used neuronal markers to characterize new cells at different time points after cell division. In the neocortex and striatum, we found BrdU-labeled cells that expressed each of the eight neuronal markers. Their size as well as staining for γ-aminobu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
394
4
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(434 citation statements)
references
References 60 publications
32
394
4
4
Order By: Relevance
“…NG2 + cells have been found both in the SVZ and hippocampus, and analysis of their developmental potential has demonstrated that they are not only a source of oligodendrocytes (OLs), but also have neurogenic properties Dayer et al, 2005;Ohori et al, 2006;Rogelious et al, 2006;Tamura et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…NG2 + cells have been found both in the SVZ and hippocampus, and analysis of their developmental potential has demonstrated that they are not only a source of oligodendrocytes (OLs), but also have neurogenic properties Dayer et al, 2005;Ohori et al, 2006;Rogelious et al, 2006;Tamura et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we could not observe any newborn cells in the neocortex that acquired a neuronal phenotype. Our failure to find any newborn neurons in the mPFC might be due to the fact that we employed a significantly different BrdU-labeling protocol compared with that of Dayer et al (2005), who injected much more BrdU and used longer survival times. A more systematic analysis using different BrdU-labeling protocols, survival times and various interneuronal markers may reveal that a small subset of the newly generated cells affected by stress and antidepressant treatment could be GABAergic neurons.…”
Section: Phenotypic Analysis Of the Newborn Cellsmentioning
confidence: 99%
“…The presence of newborn neurons has been reported in various neocortical areas of adult nonhuman primates (Gould et al, 1999(Gould et al, , 2001Bernier et al, 2002), but these findings have not been replicated by other investigators (Kornack and Rakic, 2001). Interestingly, a recent study came to the conclusion that GABAergic interneurons are generated in the neocortex of adult rats (Dayer et al, 2005).…”
Section: Phenotypic Analysis Of the Newborn Cellsmentioning
confidence: 99%
“…The two primary zones of adult proliferation are the subgranular layer of the hippocampal dentate gyrus and the SVZ of the forebrain, although other zones are also thought to exist 51,52 . DCX has become a widely used marker for newly generated neuroblasts in proliferative zones in adult 14,31,53,54 .…”
Section: Role Of DCX In the Rmsmentioning
confidence: 99%